The mediating role of physical activity and quality of life in the association between knee osteoarthritis-related symptoms and physical function of post-COVID patients in Metro Manila: a study protocol - Donald Manlapaz; Jon Timothy Rivero; Eliana Caris Cabildo; Jeremy Christian Advincula; Marc Angelo Aquino; Miguel Gabriel De la Paz; Maria Paulina Duldulao; Andrea Amor Maravilla; Cyd Ahnilark Montera; Kent Stefon Tee (BMJ Open)
Introduction Knee osteoarthritis (OA) is a chronic condition affecting joint function. Regular physical activity can enhance functional capacity and reduce pain. However, there is a scarcity of studies relating to knee OA during the COVID-19 pandemic, particularly its impact on symptoms and quality of life.Methods This analytic cross-sectional study design will recruit participants aged 40 and above from Metro Manila with knee pain and COVID-19 history. The Filipino version of the Knee Injury and Osteoarthritis Outcome Score and International Physical Activity Questionnaire-Short Form will be used to assess the mediating variables.Analysis The study will employ descriptive and regression analyses for data analysis and follow the Strengthening the Reporting of Observational Studies in Epidemiology statement for reporting the data.Ethics and dissemination This study has received ethical approval from the Ethics Review Committee of the College of Rehabilitation Sciences. Study results will be disseminated through peer-reviewed journal publications and conference presentations to ensure accessibility to healthcare professionals and stakeholders, contributing to the advancement of knee OA management in post-COVID settings.